To the 75th Birthday of Professor Andrzej Jeżowski - Krivchikov, Alexander; Pikul, Adam; Dolbin, Oleksandr (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2025)
This Special Issue honors the 75th birthday of Professor Andrzej Jeżowski, a renowned expert in the thermal conductivity of solids, especially cryocrystals and nanocomposites. Professor Jeżowski is not only a leading scientist in his field but also a long-standing collaborator and close friend of the B. Verkin Institute for Low Temperature Physics and Engineering of the National Academy of Sciences of Ukraine (ILTPE NASU) in Kharkiv. He has been a committed advocate for Polish-Ukrainian scientific cooperation for many decades. This issue is our way of expressing our deep gratitude to Professor Jeżowski for his significant contributions to science and his long-term participation in developing the journal.